Physical Characterization of Breast Implants Submitted to High Energy X-Rays - Patiño Leiva, Sandra Johana; Plazas, María Cristina; Barreto, Lisette (TECCIENCIA, 2019)
Based on clinical experience and various studies, it has been found that breast prostheses present failures that are related to a radiotherapy treatment. However, there are currently few studies that analyze the impact of radiotherapy on the material of the prosthesis. Accordingly, the aim of this paper is to characterize the material of silicone breast implants with high cohesiveness. In order to carry out the research a characterization based on mechanical tests, rheology, and spectrophotometry and scanning electron microscopy. This was done with the objective of identifying changes in the prosthesis before and after being irradiated with high energy x-ray photons. To perform the study, 4 breast implants were used. These implants were subjected to the aforementioned tests. The researcher repeated the observation in the second and the third month. Finally, when comparing the results, the mechanical changes are shown in the coating. In the internal material small changes were generated in the elastic and viscous modules. To conclude, effective changes were observed after radiotherapy treatment in the prosthetic material.